Stress Wave Propagation In A ‘Simplified Surrogate Tibia’ Subjected To Blast Loading - Seenzayi, Davison (Department of Mechanical Engineering, 2024)
Landmines are a continuous and serious threat to mankind, resulting in thousands of casualties globally each year. Casualties have risen due to the proliferation of improvised explosive devices (IEDs), cluster munition remnants, and other explosive remnants of war. In these terrible occurrences, both the civilians and military and security personnel suffer great losses. Despite anti-mine awareness programs and the development of new mitigating measures, the number of landmine victims continues to rise. While anti-vehicle and anti-personnel landmines offer major hazards, anti-vehicle landmines create much larger energy transfers than anti-personnel landmines, resulting in more severe and complicated lower limb injuries frequently presenting distinct rehabilitation issues. Understanding the mechanics leading to tibia injuries in anti-vehicle landmine occurrences helps develop and enhance safety and well-being of vehicle occupants exposed to anti-vehicle landmine blast scenario. The study of stress wave propagations in the tibia during an anti-vehicle landmine blast aids in scientific understanding of blast injuries produced by anti-vehicle landmines by refining current ideas, discovering novel phenomena, and filling information gaps. This study aimed to understand the stress wave propagation through the tibia caused by an anti-vehicle landmine explosion. Simplified tibia models were developed and used in an experimental approach for capturing blast-induced stress wave propagations through the tibia. The floor of a vehicle was represented by deformable and nondeformable witness plates. Aluminium tubular structures were used to develop simplified surrogate tibia models with different cross-sections which used to calibrate a Finite Element Model (FEM). Strain gauges were installed on the centre of tubular structure to record the direct stress induced by the blast load. A numerical model, developed using LS-Dyna software, was validated using the experimental blast test stress results on the tubular structures. Once validated, the numerical model was updated by replacing the tubular structures with a 3D CAD tibia. The replacement of tubular structures with tibia model was undertaken to enable the investigation of stress distribution within the tibia with greater precision and accuracy. A parametric study was, thereafter, carried out investigating the effect of geometry on stress propagations and its correlation with associated injuries. The parametric study successfully explored the blast induced stress waves propagations and its distribution within the tibia model during a blast event. The tibia model experienced a compressive load cycle followed by a tensile load cycle as the stress waves got reflected upon encountering boundaries. Analysis of stress-time response graphs revealed the highest strain levels at the interface between the tibia model and the witness plate, indicating greater susceptibility to blast injuries in the lower extremities, particularly at the point of contact. In the numerical simulations aluminium was implemented as the “bone” material for simplification. It should be noted that bone is a complex composite material which is hard to characterise and not considered in the scope of this study. The focus of this study was to gain an understanding how the stress wave resulting from the blast load would propagate in a structure with varying geometries such as a tibia and analysis of the peak stresses. The information gained from these simulations provided valuable insights into injuries caused by blast and their potential effects on the tibia when subjected to anti-vehicle landmine explosions. The severity of the injury depends on the material properties and geometry of the tibia. Additionally, the study explored the effect of deformable and non-deformable witness plate on the load transmitted to the tibia, resulting in different injury mechanisms and patterns.